2017
DOI: 10.1117/1.jbo.22.10.106016
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal spectral-domain optical coherence tomography based on Bessel beam for extended imaging depth

Abstract: To advance the practical application of optical coherence tomography (OCT) in the field of biomedical imaging, the imaging depth must be extended without sacrificing resolution while maintaining sufficient sensitivity. However, there is an inherent trade-off between lateral resolution and depth of field (DOF) in OCT. To address this shortcoming, this article proposes a multifocal Bessel beam spectral-domain optical coherence tomography (MBSDOCT) capable of increasing the DOF with unchanged lateral resolution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…OCT combined with Bessel beams has been shown to enable a large depth range of over 6 mm [ 80 ]. Several OCT modalities utilizing Bessel beams for high-resolution imaging have been reported [ 80 , 81 , 82 , 83 ]. However, there have not been many reports demonstrating their application in ophthalmic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…OCT combined with Bessel beams has been shown to enable a large depth range of over 6 mm [ 80 ]. Several OCT modalities utilizing Bessel beams for high-resolution imaging have been reported [ 80 , 81 , 82 , 83 ]. However, there have not been many reports demonstrating their application in ophthalmic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…To extend the depth of focus in OCT imaging, typical hardware approaches, such as binary phase-spatial filters (Kim et al 2017), multi-beam method (Standish et al 2010), and axicons (Yi et al 2017), have been suggested to improve defocus. Compared to hardware-based methods, signal processing methods provide alternative and flexible solutions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Using the Maxwell equations for the OCT simulations is suitable for modeling complex (profiled) laser beams. [24][25][26][27][28][29] However, it is very time-consuming, even using parallel algorithms, [30][31][32] and requires allocation of massive computer resources that significantly limits the spatial area of interest.…”
Section: Introductionmentioning
confidence: 99%